Functional Characterization of Entamoeba histolytica Argonaute Proteins Reveals a Repetitive DR-Rich Motif Region That Controls Nuclear Localization - Hanbang Zhang; Vy Tran; Dipak Manna; Gretchen Ehrenkaufer; Upinder Singh (mSphere, 2019)
ABSTRACT The RNA interference (RNAi) pathway regulates gene expression in many eukaryotic organisms. Argonaute (Ago) proteins, together with bound small RNAs (sRNAs), are key effectors that mediate gene silencing function. However, there is limited knowledge of Ago proteins and their functions in nonmodel systems. In the protozoan parasite Entamoeba histolytica, RNAi is a robust means for stable gene silencing mediated via large populations of antisense sRNAs. Here, we report functional characterization of three Ago proteins in E. histolytica (EhAgo2-1, EhAgo2-2, and EhAgo2-3). Our data show that each EhAgo protein has a distinct subcellular localization and binds 27-nucleotide (nt) sRNAs and that the localization of EhAgo proteins is altered in response to stress conditions. Via mutagenesis analyses, we demonstrated that the Ago PAZ (Piwi/Argonaute/Zwille) domain in all three EhAgos is essential for sRNA binding. With mutation of the PAZ domain in EhAgo2-2, there was no effect on the nuclear localization of the protein but a strong phenotype and a growth defect. We further show that EhAgo2-2 contains an unusual repetitive DR-rich (aspartic acid, arginine-rich) motif region which functions as a nuclear localization signal (NLS) and is both necessary and sufficient to mediate nuclear localization. Overall, our data delineate the localization and sRNA binding features of the three E. histolytica Ago proteins and demonstrate that the PAZ domain is necessary for sRNA binding. The repetitive DR-rich motif region in EhAgo2-2 has not previously been defined in other systems, which adds to the novel observations that can be made when studies of the RNAi pathway are extended to nonmodel systems. IMPORTANCE The protozoan parasite Entamoeba histolytica, which causes amebiasis and affects over 50 million people worldwide, contains an important RNAi pathway for gene silencing. Gene silencing via the RNAi pathway is mediated by the Argonaute (Ago) proteins. However, we lack knowledge on Ago function(s) in this nonmodel system. In this paper, we discovered that three E. histolytica Ago proteins (EhAgo2-1, EhAgo2-2, and EhAgo2-3) all bind 27-nt small RNAs and have distinct subcellular localizations, which change in response to stress conditions. The EhAgos bind small RNA populations via their PAZ domains. An unusual repetitive DR-rich motif region is identified in EhAgo2-2 that functions as a nuclear localization signal. Our results show for the first time an active nuclear transport process of the EhAgo2-2 RNA-induced silencing complex (RISC) in this parasite. These data add to the novel observations that can be made when studies of the RNAi pathway are extended to nonmodel systems.